2013
DOI: 10.1017/s1049023x13000241
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Mass-Casualty Triage Training—Written Versus Moulage Scenarios: How Much Do EMS Providers Retain?

Abstract: These data confirm the skill deterioration associated with an infrequently used triage method. Further research to more precisely define triage criteria, as well as the ability to apply the criteria in a clinical setting and to rapidly identify patients at risk for morbidity/mortality is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 47 publications
3
39
1
1
Order By: Relevance
“…The same authors subsequently investigated knowledge retention in another START triage study comparing scores immediately post-training and those six months later in both written and simulated scenarios. 18 In their written scenarios, a statistically significant drop in triage accuracy from 73.3% to 65.0% was found, whereas a significant reduction from 65.0% to 60.0% was reported in simulated scenarios. However, a 2011 study by Deluhery et al found no significant decline in triage accuracy when comparing post-training test scores and those occurring four months after.…”
Section: Discussionmentioning
confidence: 82%
“…The same authors subsequently investigated knowledge retention in another START triage study comparing scores immediately post-training and those six months later in both written and simulated scenarios. 18 In their written scenarios, a statistically significant drop in triage accuracy from 73.3% to 65.0% was found, whereas a significant reduction from 65.0% to 60.0% was reported in simulated scenarios. However, a 2011 study by Deluhery et al found no significant decline in triage accuracy when comparing post-training test scores and those occurring four months after.…”
Section: Discussionmentioning
confidence: 82%
“…The fact that a sizable proportion of the articles was published in 2012 indicates that the Pyramid and its percentages are still currently being cited in medical education literature. Further, the error is being reinforced in new articles and books dealing with medical education (Frith 2013;Risavi et al 2013;Sewell 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, planning and management are the most critical elements for optimal allocation of limited resources in such incidents [5]. Management of these conditions is a complex process that includes coordination of therapeutic interventions and effective triage [6][7][8]. This V objective will be achieved if health centers are at least prepared for different incidents [9].…”
Section: Introductionmentioning
confidence: 99%